BIVOLARU, A., COTTICA, D., MORHANGE, C. (EDS.), Waterscapes Archaeology. Multi-Scalar Human-Environment Interactions in Coastal Lagoons. Archaeopress. - García Sanchez, Jesús (Riparia, 2026)
Reseña del libro: Waterscapes Archaeology. Multi-Scalar Human-Environment Interactions in Coastal Lagoons. Archaeopress.